Technology Instruction For Children With Learning Disabilities In Mathematics: Teacher’s Views (Sains Humanika, 2017)
The purpose of this paper is to examine the perspective of teachers regarding mathematics instruction for children with learning disabilities. For this purpose, a semi-structured interview was conducted with teachers who teach mathematics to children with learning disabilities. The participants of this study are three educators who teach children with learning disabilities. A qualitative strategy approach is used in this study using case studies. Information was acquired from interviews, document reviews and Brainstorming. The method of analysis involves the data transcription process, construction of themes, theme coding and displaying. The results of the research is analysed and recommendation for future research is stated. Intervention for children with Learning Disabilities is a challenge for both teachers and parents. Children with Learning Disabilities require special instructions in order to succeed and technology can help children depends on situation and teaching style.
Keywords: Instruction; learning disabilities; mathematics